Tunable axial bursts using annularly distributed phase masks - Ojeda Castaneda, Jorge; Ledesma, Sergio; Gomez Sarabia, Cristina Margarita (Photonics Letters of Poland, 2012)
We identify a family set of fractional power, annularly distributed phase-masks for generating axial irradiance bursts. We show that by changing the phase delay, for certain fractional power, one can generate either short tail or long tail axial irradiance bursts. To this end, we discuss the use of a pair of angularly modulated, Alvarez-Lohmann lens. Full Text: PDF References C. W. McCutchen, "Generalized Aperture and the Three-Dimensional Diffraction Image", J. Opt. Soc. Am. 54, 240-244 (1964) CrossRef C. W. McCutchen, "Convolution relation within the three-dimensional diffraction image", J. Opt. Soc. Am. A 8, 868–870 (1991). CrossRef C. W. McCutchen, "Generalized aperture and the three-dimensional diffraction image: erratum", J. Opt. Soc. Am. A 19, 1721-1721 (2002). CrossRef J. Ojeda-Castaneda, P. Andrés and A. Díaz, "Annular apodizers for low sensitivity to defocus and to spherical aberration", Opt. Lett. 11, 487- 489 (1986). CrossRef J. Ojeda-Castaneda, L. R. Berriel-Valdos and E. Montes, "Bessel annular apodizers: imaging characteristics", Appl. Opt. 26, 2770-2772 (1987). CrossRef J. Ojeda-Castaneda, P. Andrés and A. Díaz, "Strehl ratio with low sensitivity to spherical aberration", J. Opt. Soc. Am. A 5, 1233-1236 (1988). CrossRef J. Ojeda-Castañeda, and A. Díaz, "High focal depth by quasibifocus", Applied Optics 27, 4163-4165 (1988). CrossRef A. Kołodziejczyk, S. Bara, Z. Jaroszewicz, and M. Sypek, "The Light Sword Optical Element—a New Diffraction Structure with Extended Depth of Focus", J. Mod. Opt. 37, 1283-1286 (1990). CrossRef J. Ojeda-Castañeda, M. Martínez-Corral and P. Andrés, "Zero axial irradiance by annular screens with angular variation", Appl. Opt. 31, 4600-4602 (1992). CrossRef J. Sochacki, S. Bara, Z. Jaroszewicz, and A. Kołodziejczyk, "Phase retardation of the uniform-intensity axilens", Opt. Lett. 17, 7-9 (1992). CrossRef J. Ojeda-Castañeda and G. Ramírez, "Zone plates for zero axial irradiance", Opt. Lett. 18, 87-89 (1993). CrossRef J. Ojeda-Castañeda, M. Martínez-Corral, P. Andrés and A. Pons, "Strehl ratio versus defocus for noncentrally obscured pupils", Appl. Opt. 33, 7611-7616 (1994). CrossRef A. W. Lohmann, Italian patent 727,848 (June 19, 1964). L. W. Alvarez, U.S. patent 3,305,294 (December 3, 1964). A. W. Lohmann, British patent 998,191 (May 29, 1965). A. W. Lohmann and D.P. Paris, "Variable Fresnel Zone Pattern", Appl. Opt. 6, 1567-1570 (1967). CrossRef I. A. Palusinski, J.M. Sasian, and J.E. Greivenkamp, "Lateral-Shift Variable Aberration Generators", Appl. Opt. 38, 86-90 (1999). CrossRef G. Mikuła, Z. Jaroszewicz, A. Kolodziejczyk, K.Petelczyc and M. Sypek, "Imaging with extended focal depth by means of lenses with radial and angular modulation", Opt. Exp. 15, 9184-9193 (2007). CrossRef J. Ojeda-Castaneda, J. E. A. Landgrave and C. M. Gómez-Sarabia, "Conjugate phase plate use in analysis of the frequency response of imaging systems designed for extended depth of field", Appl. Opt. 47, E99 – E105 (2008). CrossRef Angel Sauceda and J. Ojeda-Castaneda, "High focal depth with fractional-power wave fronts", Opt. Lett. 29, 560-562 (2004). CrossRef Albertina Castro and J. Ojeda-Castaneda, "Asymmetric Phase Masks for Extended Depth of Field", Appl. Opt. 43, 3474-3479 (2004). CrossRef N. Brenner and C. Rader, "A new principle for fast Fourier transformation", IEEE Acoustics, Speech & Signal Processing 24, 264–266 (1976). CrossRef J. Ojeda-Castañeda, J. E. A. Landgrave and H. M. Escamilla, "Annular phase-only mask for high focal depth", Opt. Lett. 30, 1647-1649 (2005). CrossRef